Dexamethasone as Prophylaxis of Postoperative Nausea and Vomiting in Cardiothoracic Surgery: Systematic Review and Meta-Analysis - Wibowo, Marcell Dion; Ratumasa, Marilaeta Cindryani Ra; Ningrat, I Ketut Jaya; Adi, Made Septyana Parama; Krisnayana, Anak Agung Gede (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif (PERDATIN) / The Indonesian Society of Anesthesiology and Intensive Care (INSAIC), 2025)
Introduction: Postoperative nausea and vomiting (PONV) remain common and distressing complications following surgery, particularly after high-risk procedures such as cardiothoracic surgeries. Dexamethasone, a corticosteroid with anti-inflammatory and antiemetic effects, has been widely investigated for its role in PONV prevention. This study aimed to evaluate the efficacy of dexamethasone in reducing the incidence of PONV among patients undergoing cardiothoracic surgery through a systematic review and meta-analysis. Methods: The systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. Randomized Controlled Trials (RCTs) comparing dexamethasone with placebo or no intervention in cardiothoracic surgery were included. The primary outcome was the incidence of PONV within 24 hours postoperatively; secondary outcomes included the need for rescue antiemetics and the occurrence of adverse effects such as hyperglycemia or infection. Statistical analysis was conducted using Review Manager 5.4, with heterogeneity assessed by the I² and Q/df tests. Results: Four RCTs published between 2018 and 2023 were included, showing low risk of bias and symmetrical funnel plots. The pooled analysis demonstrated a statistically significant reduction in PONV with dexamethasone (OR = 0.57, 95% CI = 0.41–0.80, p = 0.001, I² = 9%, Q/df = 0.98). Conclusion: Dexamethasone significantly reduces the incidence of PONV in patients undergoing cardiothoracic surgery with consistent findings across studies. Further large-scale RCTs are needed to confirm long-term safety and optimize clinical protocols.